Moderasi Inklusi Keuangan Terhadap Hubungan Literasi Keuangan dan Keputusan Struktur Modal UKM - Muhammad Irfai Sohilauw (JBIMA (Jurnal Bisnis dan Manajemen), 2018)
TThis study aims to explain the relationship between financial literacy and the capital structure decisions of SME debtors which are moderated by financial inclusion. This research is an explanatory research in the city of Makassar. The population taken is all traditional market entrepreneurs of SMEs in Makassar City. The selection of research samples uses a non-probability sampling method with a clustering method and stratified random sampling. With the help of SPSS software, data were analyzed using descriptive and inferential statistical methods. The results obtained are financial inclusion strengthening the relationship of Financial Literacy with the SME capital structure decision in Makassar City.